Dinamika Reformasi Birokrasi Indonesia - dwi putri, nur aslamaturrahmah (Kemudi, 2016)
Bureaucracy is an the important element to created a Good Governance. A Good or bad country is depend on the bureaucracy. To create a good governance is not an easy thing, in the future the bureaucracy will be facedsome Challenge that come from in the country and from abroad. However, the condition of Indonesian bureaucracy previously is still far from expectations, like the services still bad, and the corruption still grow up. Therefore, we needed an effort to changes the condition that we call bureaucratic reform, but until now the bureaucratic reform running slowly, the dynamics of Bureaucracy reform keep walking from one step to the step and of course will be appeared some problem inside. Because to change indonesia bureaucracy which is still used the patrimonial bureaucracy is not the easy thing, bureaucrcy reform must be running with involves all aspects which influence the bureaucracy reform such as economic,political and sosial culture and the stakeholders must be related bureaucracy reform to completed all the public problem.